Habilidades sociais em portadores de anomalia da diferenciação sexual - SARDINHA, Ana Paula de Andrade (Universidade Federal do Pará, 2014)
The term Social Skills (SS) is used to describe a set of behavioral repertoires that involve social interactions satisfactory. Most published studies on this topic include the participation of children and adolescents by addressing situations in the school environment. Few studies have focused on the health area, and, so far, it has not been found surveys on SS conducted with individuals with the Anomaly of Sex Differentiation (ASD). This anomaly is characterized by malformations in the genitals and/or dysfunction of the gonads, causing secondary sexual characteristics which do not correspond to the sex of rearing. Clinical studies with individuals with ASD have highlighted the occurrence of deficits in social skills in these individuals, characterized by the escape-avoidance of aversive social situations. In this study, we sought to characterize the behavioral repertoire corresponding to SS in individuals with ASD treated at an outpatient clinic of a specialized program developed in a public hospital in Belém, through two complementary studies. At first, we performed a cross-sectional study, with the aim of characterizing the behaviors corresponding to SS in individuals with ASD. The participants were 9 adults in treatment for more than six months. Were used: Interview Script, Protocol for review of medical records and Social Skills Inventory - SSI. The results suggest that the participants have social skills deficits in all the factors of the SSI to a lesser or greater degree, so that could benefit from a social skills training as part of the treatment because it is a technique that aims at overcoming and/or reducing the deficits produced by them. In the second part, a study with a single subject design was performed seeking for evaluating the effects of using self-monitoring training in the installation of behaviors corresponding to SS. Attended an adult woman diagnosed with ASD selected among those who participated in Study 1. The intervention procedure was conducted through weekly interviews, according to the following steps: (1) Agreement: signing the consent form and scheduling an appointment, (2) Evaluation: Baseline survey of behaviors corresponding to SS, preparation of the hierarchy of behaviors that indicate a deficit, under the analysis rules of the SSI, and training in self-monitoring record, (3) Intervention: reading a text on social skills, presentation of the list of basic human rights, application of the adapted Goldiamond’s Constructional Questionnaire, and training in self-monitoring record, (4) Re-evaluation of the SS: reapplication of the SSI; (5) Follow-up: assessing the maintenance of the gains to the study, and (6) Closing: return interview in order to explain the results of the study to the participant. The results suggest that the intervention promoted the development of SS in the participant, given the interpretation of the participant’s evolution presented in accordance with the variation of Z score and the graphical representation of reliable change and clinical significance.